Global diversity and phylogeny of Incrustoporiaceae (Polyporales, Basidiomycota) with an emphasis on Skeletocutis - Zhan-Bo Liu; Hong-Gao Liu; Josef Vlasák; Genevieve M. Gates; Zhen-Hao Li; Yu-Cheng Dai; Yuan Yuan (Mycology)
This study presents the taxonomy and phylogeny of the family Incrustoporiaceae, based on comprehensive phylogenetic analyses utilising multi-gene data, including the internal transcribed spacer regions (ITS) and the large subunit of the nuclear ribosomal RNA gene (nLSU), for the accepted genera within Incrustoporiaceae. Additionally, a separate phylogenetic analysis focusing on the Skeletocutis nivea complex was performed using ITS sequences. A total of 20 new species within the genus Skeletocutis are described, namely Skeletocutis crystallina, S. cunninghamiae, S. cylindrica, S. ellipsoidea, S. flavipora, S. latemarginata, S. liangdongii, S. monocotyledona, S. montanus, S. neoalbomarginata, S. oceanica, S. ochraceocarpa, S. quercicola, S. sinica, S. sinoalbomarginata, S. sinochrysella, S. subamorpha, S. subdiluta, S. subkrawtzewii, and S. sublilacina. Detailed illustrated descriptions, voucher specimens, hosts, distribution, diagnoses, and remarks are provided for these 20 new species. Additionally, two new combinations are proposed: S. minutula and Tyromyces subodorus. Notably, our discoveries of S. oceanica and S. subdiluta in Australia underscore the significance of expanding research on Skeletocutis diversity in the Southern Hemisphere, where reports are scarce. Phylogenetic analyses also clarified the taxonomic positions of Skeletocutis and Tyromyces within the Incrustoporiaceae family, showing that Tyromyces is nested within the polyphyletic Skeletocutis clade. The morphological distinctions between Skeletocutis and Tyromyces, as well as between Skeletocutis and Sidera, are also discussed.